Low serum vitamin D levels are associated with shorter survival after first-line azacitidine treatment in patients with myelodysplastic syndrome and secondary oligoblastic acute myeloid leukemia - Radujković, Aleksandar; Schnitzler, Paul; Ho, Anthony Dick; Dreger, Peter; Luft, Thomas (Clinical nutrition, 2017)
Summary: Background & aims: Azacitidine (AZA) therapy has become the recommended first-line treatment for patients with high-risk myelodysplastic syndromes (MDS) and oligoblastic (<30% bone marrow blasts) acute myeloid leukemia (AML). However, improvement of the efficacy of AZA treatment remains a challenge. We retrospectively tested the hypothesis that VitD levels (25-hydroxyvitamin D3) prior to start of first-line AZA therapy are predictive of overall survival (OS) in patients diagnosed with MDS and secondary oligoblastic AML. Furthermore, the antiproliferative effects of AZA in combination with 25-hydroxyvitamin D3 and 1α,25-dihydroxyvitamin D3 were investigated in vitro. Methods: A total of 58 patients treated at our center between 2006 and 2014 were analyzed. Serum levels of VitD were quantified using a standard, commercially available 25-hydroxyvitamin D3 chemiluminescent immunoassay. Effects on cell proliferation were assessed using tetrazolium-based MTT assays. Results: Median serum VitD level prior to AZA treatment was 32.8 nM (range 11.0-101.5 nM). Patient, disease and treatment characteristics did not differ significantly between the low (≤32.8 nM; n = 29) and high (>32.8 nM; n = 29) VitD group. Estimated probability of 2-year OS in the low versus high VitD group was 14% versus 40% (P < 0.05). In multivariable analysis with OS as endpoint, adverse cytogenetics (HR 2.66, P = 0.03) and VitD (per 10 nM decrease, HR 1.68, P = 0.02) were independent predictors of worse survival. In-vitro treatment of myeloid cell lines with AZA in combination with VitD produced synergistic and additive antiproliferative effects. Addition of nanomolar VitD concentrations to AZA resulted in potentiation of AZA activity. Conversely, combination with the VitD antagonist TEI-9647 resulted in inhibition of AZA activity. Conclusions: Our study suggests that higher VitD levels were associated with a survival advantage following first-line AZA therapy. Enhanced cytotoxic effects upon combination treatment may contribute to the observed clinical effects. VitD repletion/supplementation during AZA treatment should be explored.